MEMBANGUN-KERUKUNAN ANTARUMAT BERAGAMA DI MADIUN MELALUI DIALOG KEHIDUPAN DALAM TERANG NOSTRA AETATE - Ola Rongan Wilhemus; Prima Novaliasari (Bahasa Indonesia, 2019)
Indonesia is a country consist of various tribes, languages, customs, and religions. This diversity is a treasure of the country which is worthy to be proud. However this diversity can also lead to a conflict. In Indonesia it has been an evident proof that many conflicts were caused by religious differences. Based on the experience of inter-religious conflicts, anyone as a citizen wish an inter-religious harmony which transcends the religious differences in Indonesia. Inter-religious harmony present at atmosphere of brotherhood and a sense of unity among the religion followers. Inter-religious harmony can also be defined as a process to achieve a state of living in harmony and peace in despite of the differences in religion. By means of the inter-religious dialogue of life, a person can develop him/herself in terms of knowledge and tolerant attitudes in the daily life. This study used qualitative research method directed to answer the research question: How far do the members of the Forum of the Inter-Religious Harmony (FKUB) and all the people who are actively involved, as the informants, live the implementation of the dialogue of life in the daily life, and how far do the main subjects of Nostra Aetate appraise the implementation of a dialogue of life in the region of Madiun? The result of this research generaly reveal that the informants have lived the implementation of inter-religious dialogue in the daily life. the informant to achieve the inter-religious harmony in Indonesia. It means that the main views of Nostra Aetate have been internalized by the most people.